2020
DOI: 10.1504/ijenm.2020.103913
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise big data analysis using SVM classifier and lexicon dictionary

Abstract: The emergence of the digital era has led to growth in various types of data in a cloud. In fact, there may be three fourth of the total data will be treated as big data. In many organisations, massive volume of both structured and unstructured data sit idle. Various categories of data are complex for pre-processing, analysing, storing and visualising. Cloud computing provides suitable platform for big data analytics for the storage and for predicting customer behaviour to sell products. Unstructured data like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In conclusion, introduction of advanced analytics tools to predict consumer buying behaviors is also seen as moderately reported in the existing literature (Huang & Mieghem, 2013;Kitchens et al, 2018;Marinelli et al, 2020;Martínez et al, 2020;Miles, 2014;Radha & Babu, 2020).…”
Section: Industrymentioning
confidence: 85%
See 1 more Smart Citation
“…In conclusion, introduction of advanced analytics tools to predict consumer buying behaviors is also seen as moderately reported in the existing literature (Huang & Mieghem, 2013;Kitchens et al, 2018;Marinelli et al, 2020;Martínez et al, 2020;Miles, 2014;Radha & Babu, 2020).…”
Section: Industrymentioning
confidence: 85%
“…Several scholars identified the importance of maintaining a quality database in their organizations (Ibrahim & Wang, 2019;Kakatkar & Spann, 2019;Li et al, 2020;Maheshwari et al, 2020;Silva et al, 2019). Further, it was identified that the quality datasets helped forecast the firms' future with more accurate predictions (Huang & Mieghem, 2013;Martínez et al, 2020;Radha & Babu, 2020;Reutterer et al, 2020). It was identified that advances in machine learning and consumer culture could affect the revenue, margins, and market share of a firm (Pantano, 2020;Pantano & Dennis, 2019;Pantano et al, 2019;Simchi-Levi & Wu, 2018).…”
Section: Independent Variables (Ivs)mentioning
confidence: 99%